PERANCANGAN DAN IMPLEMENTASI SISTEM INFORMASI AKADEMIK SEKOLAH DASAR DAN MENENGAH PERTAMA BERBASIS WEB - Manase Sahat H Simarangkir (Electro Luceat, 2022)
Ma'had Ar-Risalah Al-Atsari is an educational institution under the auspices of the Thullab Charity Foundation. In the process of registering new students it is still done conventionally, causing problems in managing registration data, sometimes people have difficulty getting information to carry out the registration process and get information about the school. The administrative process also tends to be slow, because the data has not been integrated and managed properly. This process also still uses archives in physical form that are prone to damage or even loss. The collection of teacher data or files is still via flash drive. Therefore we need an information system that can help deal with this problem by building a Web-Based Elementary and Junior High School Academic Information System (Case Study of Ma'had Ar-Risalah Al-Atsari). The method used for the development of the information system uses the extreme programming method with an object-oriented system approach that is modeled using UML (Unified Modeling Language). The end result of the development of this information system is the existence of a system that can facilitate the community in registering, the administration of new student admissions becomes more effective and efficient, the public can find out information about schools through the website, for teachers to collect files or other data. can be more effective and efficient, for parents to be able to check student report cards at any time without having to wait for the distribution of report cards, this system can be used to replace archiving school data.